Indonesian Secondary School Students’ Happiness at the Beginning of Covid-19 Pandemic (International Journal of Theory and Application in Elementary and Secondary School Education, 2021)
Happiness is a subjective assessment of individual wellbeing. Adolescents, especially secondary school students living in Islamic Boarding School, experience dramatic changes from learning at their dormitory with face-to-face teaching method to distance learning at home with minimum activities outside their houses. The survey was conducted on 111 respondents of students who had to return home due to the outbreaks of covid-19 pandemic for two months. The research found that the dramatic changes made them had difficulty to adapt new activities at home for a long time while studying independently through distance learning. Only a third of the sample felt happy during the online learning while the majority felt negative emotions such as boredom, unhappiness, and loneliness. The adolescents’ life satisfaction and community engagement significantly correlated with happiness although the size effects were medium. Female students also had lower happiness variables than males. To maintain their happiness, during the pandemic, most of them prefer activities that mostly trigger a sedentary lifestyle.